Ten‐year attrition and antiretroviral therapy response among HIV‐positive adults: a sex‐based cohort analysis from eight West African countries. Issue 5 (21st May 2021) - Tiendrebeogo, Thierry; Messou, Eugène; Arikawa, Shino; Ekouevi, Didier K; Tanon, Aristophane; Kwaghe, Vivian; Balestre, Eric; Zannou, Marcel Djimon; Poda, Armel; Dabis, François; Jaquet, Antoine; Minga, Albert; et al.
Abstract: Introduction: Sex differences have already been reported in sub‐Saharan Africa for attrition and immunological response after antiretroviral therapy (ART) initiation, but follow‐up was usually limited to the first two to three years after ART initiation. We evaluated sex differences on the same outcomes in the 10 years following ART initiation in West African adults. Methods: We used cohort data of patients included in the IeDEA West Africa collaboration, who initiated ART between 2002 and 2014. We modelled no‐follow‐up and 10‐year attrition risks, and immunological response by sex using logistic regression analysis, survival analysis with random effect and linear mixed models respectively. Results: A total of 71, 283 patients (65.8% women) contributed to 310, 007 person‐years of follow‐up in 16 clinics in eight West African countries. The cumulative attrition incidence at 10‐year after ART initiation reached 75% and 68% for men and women respectively. Being male was associated with an increased risk of no follow‐up after starting ART (5.1% vs. 4.0%, adjusted Odds Ratio: 1.25 [95% CI: 1.15 to 1.35]) and of 10‐year attrition throughout the 10‐year period following ART initiation: adjusted Hazard Ratios were 1.22 [95% CI: 1.17 to 1.27], 1.08 [95% CI: 1.04 to 1.12] and 1.04 [95% CI: 1.01 to 1.08] during year 1, years 2 to 4 and 5 to 10 respectively. A better immunological response was achieved by women than men: monthly CD4 gain was 30.2 and 28.3 cells/mL in the first four months and 2.6 and 1.9 cells/μL thereafter. Ultimately, women reached the average threshold of 500 CD4 cells/μL in their sixth year of follow‐up, whereas men failed to reach it even at the end of the 10‐year follow‐up period. The proportion of patients reaching the threshold was much higher in women than in men after 10 years since ART initiation (65% vs. 44%). Conclusions: In West Africa, attrition is unacceptably high in both sexes. Men are more vulnerable than women on both attrition and immunological response to ART in the 10 years following ART initiation. Innovative tracing strategies that are sex‐adapted are needed for patients in care to monitor attrition, detect early high‐risk groups so that they can stay in care with a durably controlled infection.